2017
DOI: 10.1002/14651858.cd012780
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and cost-effectiveness of inpatient specialist palliative care in acute hospitals for adults with advanced illness and their caregivers

Abstract: How many people need palliative care? A study developing and comparing methods for populationbased estimates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…We changed the single primary outcome of pain in the published protocol 46 to two primary outcomes: patient health-related quality of life (HRQoL) and patient symptom burden assessed using a composite measure of two or more symptoms. The clinical experts on our project advisory group suggested that pain may not be an appropriate primary outcome measure for studies about non-malignant conditions, for which pain may be less prevalent than for cancer.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We changed the single primary outcome of pain in the published protocol 46 to two primary outcomes: patient health-related quality of life (HRQoL) and patient symptom burden assessed using a composite measure of two or more symptoms. The clinical experts on our project advisory group suggested that pain may not be an appropriate primary outcome measure for studies about non-malignant conditions, for which pain may be less prevalent than for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the published protocol, 46 we stated that we would include a number of study designs including randomised trials, non-randomised trials, controlled before-and-after studies, interrupted time series studies and repeated-measures studies. Owing to the expansion of our review and given that RCTs are the most rigorous study design, we refrained from analysing studies that were not RCTs to reduce heterogeneity and allow meta-analyses when possible.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations